KARAKTERISTIK SIFAT MEKANIK DAN STRUKTUR MIKRO PADA MATERIAL Sn-0,7Cu-“X”Zn - Ridwan Adidarma; Erwin Siahaan; Abrar Riza (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Lead (Pb) in solder has been used for decades in industries of electronic equipment. Mostly in the lead solder old electronic equipment containing 63% (Sn), 37% lead (Pb). Heating solder in high temperature steam generating heat which can damage the respiratory system. The purpose of this analytic is to obtain the characteristics of the mechanical properties of the alloy Sn-0,7Cu- "X" Zn better than the Sn-Pb alloy as an alternative to non-lead solder alloy material. Tests conducted in the form of density, melting temperature, metallography, shear strength, and hardness. The effect of addition of Zn alloy Sn-Cu-Zn increase hardness value of each acquired 85% of the material Sn-0,7Cu-10Zn, 81% were obtained from material Sn-0,7Cu-11Zn and 70% was obtained from material Sn -0,7Cu-11Zn. While the effect of adding Zn alloy Sn-Cu-Zn can increase the shear strength of each of about 29.4% on a material- 0,7Cu-10Zn Sn, 65% in material Sn-0,7Cu-11Zn and about 140% is obtained from material Sn-0,7Cu- 12Zn.